Hunter-gatherer provisioning strategies in a landscape with abundant lithic resources (La Primavera, Santa Cruz, Argentina) - Magnin, Lucia Angelica (2015)
The aim of this paper is to generate new data on raw material sourcing of multiple activities sites at La Primavera locality to describe some provisioning strategies adopted by mobile hunter-gatherer societies, and contribute to the study of the local settlement in the wider regional context. The local structure of lithic resources is characterized; the natural distribution of useful rocks is modeled and the raw materials of artifacts from multiple activities sites are sourced. The classification and sourcing technique applied is not a determinant method, but a preliminary approach adequate to deal with a very large lithic artifact sample. The rock distribution across the landscape was analyzed using a Geographical Information Systems (GIS) for compiling the available data and estimating the distances from the sites to the sources for each raw material found in them. Based on the circulation distances and different considerations regarding the characteristic of the lithic sources, three different provisioning strategies are delineated. They suggest that settlement at the locality involved a certain permanence time that surpasses a logistic use, while keeping trade and social networks with other localities in the regional context.